The impact of pharmacist‐initiated interventions in improving acute coronary syndrome secondary prevention pharmacotherapy prescribing upon discharge. (26th February 2013) - Hassan, Y.; Kassab, Y.; Abd Aziz, N.; Akram, H.; Ismail, O.
Summary What is known and Objectives Pharmacists have the knowledge regarding optimal use of medications and the ability to influence physician prescribing. Successful interventions by a pharmacist to implement cardioprotective medications to a coronary artery disease patient's regimen would not only improve the patient's quality of care but may also increase his or her likelihood of survival. Therefore, the aim of this study was to (i) evaluate the effectiveness of pharmacist initiated interventions in increasing the prescription rates of acute coronary syndrome (ACS) secondary prevention pharmacotherapy at discharge, and to (ii) evaluate the acceptance rate of these interventions by prescribers. Methods This was a comparative study with a pre‐intervention and post‐intervention design. In the pre‐intervention phase, a retrospective cross‐sectional audit was performed. Patients with a diagnosis of acute coronary syndrome admitted to the hospital in the period from 2008 to January 2010 were identified from medical records and served as a historical control. The second phase (intervention phase) was conducted from the beginning of March to the end of September 2010. Two random samples of 190 patients with ACS were included. During the intervention phase, two hospital pharmacists made rounds with the cardiology team and gave secondary prevention recommendations when needed. The major reference for the recommendations was the Malaysian guidelines. Results and Discussion A total of 72 interventions were made by pharmacists of which drug initiation was most common (59.7%) followed by recommendations to change to another medication (23.6%) and optimization of medication dosing (16.6%). Most recommendations (72.2%) were accepted by prescribers. Majority of accepted recommendations were with β‐blockers (38.46%) followed by those with angiotensin‐converting‐enzyme inhibitors (ACEI) (28.8%). The intervention had a significant impact on the utilization rates of β‐blockers (increased from 75.8% to 84.7%, P = 0.028), angiotensin‐converting‐enzyme inhibitors/angiotensin II receptor bockers (from 65.3% to 74.7%, P = 0.044) and statins (from 91.6% to 98.4%, P = 0.002). The intervention had also led to a significant increase in the utilization rates of all these four classes together (from 42.6% to 62.6%, P = 0.001). What is new and Conclusion The study showed that the presence of a pharmacist on cardiology units increased the use of beta‐blockers, aspirin, and statins for the secondary prophylaxis of ACS